Statistical Analysis of the Physicochemical Parameters of Olive (Olea europaea L.) Ecotype Oils in the Oasis Region of Degache (Tunisia) - Ben Amar Fathi; Ben Maachia Sihem; Ayadi Mohamed (Contemporary Agriculture, 2020)
A total of seventeen olive ecotypes were identified in the oasis region of Degache (Tozeur, Tunisia). The following physicochemical parameters of their oils were studied: acidity, refraction index, polyphenol, chlorophyll and carotene contents, oleic, palmitic and linoleic acid levels and the UV absorbance (K232 and K270). The acidity, K232 and K270 parameter values were used to classify most of the olive oils considered as ‘extra virgin’. The highest carotene, chlorophyll and polyphenol contents of the olive oils examined were found to be 13.60 ppm, 9.10 ppm and 796 ppm, respectively. The oleic acid level of the olive oils considered ranged between 47% and 73%, whereas the palimtic acid level ranged between 11.8% and 23%, and the linoleic acid level ranged between 8.8% and 22.5%. Therefore, the fatty acid composition of the most olive oils considered was in keeping with the IOC norms. The Pearson correlation coefficients obtained were found to be negatively significant for the oleic, palmitic and linoleic acid levels recorded. The cluster and principal component analyses performed revealed the importance of fatty acids and polyphenol contents in the clustering of olive ecotypes. The selection of olive ecotypes according to oil quality is possible, requiring further studies focusing especially on their agronomic characters.